Attitude and Practice on Herbal Usage for Prevention and Management of COVID-19 among Diabetic Patients at Tertiary Hospital in Sri Lanka - Sinnadurai, Thuvaragan; Bushra, Careem Deen Fathima; Hanza, Mohamed Aliyar Fathima; Rachel, Opatha Kanganamge Shelomi; Sanmugarajah, Vinotha (Indian Journal of Pharmacy Practice)
Background: Herbal medicine usage is common amongst people in the COVID-19 pandemic. Sri Lanka has a rich history of using herbs to treat various diseases, which is embedded in an Indigenous system of medicine. The existence of diabetes as a risk factor for COVID-19 creates a greater tendency among diabetic patients to use herbal usage. Aim: The study aims to describe the attitudes and practice of herbal usage and associated factors on herbal usage among patients with diabetes at a tertiary hospital in Sri Lanka. Materials and Methods: It is a hospital-based cross-sectional descriptive study. Four hundred and twenty-seven patients with diabetes were included in this study. Data were collected using an interviewer-administered questionnaire and data extraction form and analyzed using SPSS version 23. The chi-square test was used to assess the association between herbal usage and factors at the 95% confidence interval and a p-value less than 0.05 was considered a significant association. Results: Out of 427 patients, 72.1% used herbals to prevent and manage COVID-19. Coriander and ginger were the most commonly used herbals. Only 27.3% of patients revealed their herbal usage to the doctor. Socio-demographic factors such as Education level (0.000) had a significant association with herbal usage. Additionally, the disease-related factors such as duration of disease (0.041) and complication of diabetes (0.039) had a significant association with herbal usage. Conclusion: Most of the patients have a positive attitude towards herbal usage. Healthcare professionals should be aware of the patient’s herbal usage, especially among diabetic patients with low level of education, having diabetic complications and having diabetes for a long period when treating them.
Keywords: Herbal usage; Attitude; Practice; Diabetes; Patients; COVID 19; Sri Lanka